2020
DOI: 10.3390/ijerph17103744
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate Knowledge, Attitude and Practices about Second-Hand Smoke among Non-Smoking Pregnant Women in Urban Vietnam: The Need for Health Literacy Reinforcement

Abstract: The rate of exposure to second-hand smoke (SHS) is relatively high in several countries, including Vietnam, and health issues related to SHS have worsened in recent years, especially for pregnant women and their infants. Enhancement of knowledge, attitude, and practice (KAP) scores of pregnant women in Vietnam could raise practical interventions to protect their health and reduce complications of SHS. A cross-sectional study of 432 pregnant women who came to the Obstetrics Department of Bach Mai Hospital, Hano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…First, Vietnam has developed and effectively implemented a variety of smoke-free environment models, but recent study done in Vietnam indicates that there is a low perceived degree of compliance with smoke-free legislation by customers in restaurants 17 and inadequate degree of knowledge of SHS. 20 Second, the Tobacco Harm Prevention Law was promulgated in 2012 is only a partial ban, rather than a comprehensive ban as suggested by WHO Framework Convention on Tobacco Control. Conversely, evidence from Europe indicates that comprehensive smoking bans have a greater impact on policy support than partial smoking bans.…”
Section: Discussionmentioning
confidence: 99%
“…First, Vietnam has developed and effectively implemented a variety of smoke-free environment models, but recent study done in Vietnam indicates that there is a low perceived degree of compliance with smoke-free legislation by customers in restaurants 17 and inadequate degree of knowledge of SHS. 20 Second, the Tobacco Harm Prevention Law was promulgated in 2012 is only a partial ban, rather than a comprehensive ban as suggested by WHO Framework Convention on Tobacco Control. Conversely, evidence from Europe indicates that comprehensive smoking bans have a greater impact on policy support than partial smoking bans.…”
Section: Discussionmentioning
confidence: 99%
“… Singh and Lal (2011) referred to SHS exposure as a neglected public health challenge ( Singh and Lal, 2011 ). Vu et al (2020) demonstrated the inadequate knowledge of pregnant women in Vietnam about SHS and its health-related hazards ( Vu et al, 2020 ). Nan et al (2020) showed that women, in Inner Mongolia, Northern China, had low levels of knowledge about the dangers of SHS exposure and deplored the sparse attention provided to the education of the general public about the dangers of SHS ( Nan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Smoking remains a global health threat [ 1 , 2 ], and it is compounded by adverse relationships with depression and anxiety [ 3 ], as well as the consequences of secondhand smoke [ 4 ]. During the COVID-19 pandemic, the issue of tobacco smoking has become salient, as there is increasing evidence suggesting that smoking is associated with COVID-19 severity [ 1 ].…”
Section: Introductionmentioning
confidence: 99%